2008
DOI: 10.1055/s-2008-1027987
|View full text |Cite
|
Sign up to set email alerts
|

Die 200- bis 400 m-Brustlage dominiert bei Knieüberlastungsschäden im Schwimmsport

Abstract: Competitive swimming is a reasonable safe sport, where overuse injuries are predominant. 200 - 400 m breaststroke events increase the risk for knee overuse injuries more than other disciplines. Training for more than four times a week increases the risk twofold for knee and fourfold for shoulder overuse injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 16 publications
0
23
0
Order By: Relevance
“…In the literature, knee problems are more common in breaststroke swimmers [14]. Freestyle swimmers are at a lower risk of knee injuries [15]. Medial knee pain has been reported by up to 75% of those swimming breaststrokes [16].…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, knee problems are more common in breaststroke swimmers [14]. Freestyle swimmers are at a lower risk of knee injuries [15]. Medial knee pain has been reported by up to 75% of those swimming breaststrokes [16].…”
Section: Discussionmentioning
confidence: 99%
“…49 A survey of 341 elite swimmers showed the rate of knee injuries was 0.17 for every 1000 hours of swimming. 23 A survey of NCAA Division III college swimmers showed that females had significantly more knee injuries, as well as back/neck, shoulder, hip, and foot problems ( P < 0.01). 39 …”
Section: Epidemiologymentioning
confidence: 99%
“…23 The biomechanics of the breaststroke generates high valgus loads due to the adducted hip position. Extreme hip abduction angles at kick initiation can be detrimental.…”
Section: Epidemiologymentioning
confidence: 99%
“…28 Capaci et al 24 found the presence of back pain was associated with all 4 strokes. However, Knobloch et al 29 identified only butterfly as significantly increasing risk of pain to the cervical and lumbar spine. The level of certainty that stroke is a risk factor is low because of the limited number of studies and lack of consensus between them.…”
Section: Strokementioning
confidence: 99%